ANALISIS KONSEPTUAL NILAI DAKWAH RASULULLAH SAW DALAM PEMBELAJARAN SKI - Aulya Rahmadhani harahap; Nurzena (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to conceptually analyze the values of the Prophet Muhammad’s da’wah and their relevance to the teaching of Islamic Cultural History (SKI). The method used is a qualitative approach with a literature review design. Data was obtained from books, scientific journals, and related documents, and then analyzed using content analysis techniques. The results of the study indicate that da’wah values such as monotheism, noble character, tolerance, consultation, justice, brotherhood, peace, and exemplary conduct are highly relevant for integration into SKI instruction. These values not only strengthen students’ cognitive understanding but also shape their character and attitudes. Therefore, the conceptual integration of prophetic da’wah values into SKI instruction is essential for building a holistic Islamic education.